Commentary: Analyzing classroom dialogue to create changes in school. (April 2017) - Liberali, Fernanda
Abstract: In this commentary, the articles of the special issue will be discussed in relation to how they address classroom dialogue to promote new forms of education. The articles present possibilities to rethink learning and education through the analysis of classroom dialogue. The commentary will address how the outcomes of the included papers lead to reflections about how practitioners and researchers may rethink school and society in a more emancipating, revolutionary, and transformative way. Highlights: Articles in this special issue present possibilities to rethink learning and education through the analysis of classroom dialogue. Comments on these articles are presented from a sociosemiotic and Bakhtinian point of view. The importance of this work for creating new perspectives of classroom dialogue for the construction of new perspectives of teaching-learning in a new transformed society is emphasized.